Milk-whey diet substantially suppresses seizure-like phenotypes of paraShu, a Drosophila voltage-gated sodium channel mutant. (3rd July 2019) - Kasuya, Junko; Iyengar, Atulya; Chen, Hung-Lin; Lansdon, Patrick; Wu, Chun-Fang; Kitamoto, Toshihiro
Abstract: The Drosophila mutant para Shu harbors a dominant, gain-of-function allele of the voltage-gated sodium channel gene, paralytic ( para ). The mutant flies display severe seizure-like phenotypes, including neuronal hyperexcitability, spontaneous spasms, ether-induced leg shaking, and heat-induced convulsions. We unexpectedly found that two distinct food recipes used routinely in the Drosophila research community result in a striking difference in severity of the para Shu phenotypes. Namely, when para Shu mutants were raised on the diet originally formulated by Edward Lewis in 1960, they showed severe neurological defects as previously reported. In contrast, when they were raised on the diet developed by Frankel and Brousseau in 1968, these phenotypes were substantially suppressed. Comparison of the effects of these two well-established food recipes revealed that the diet-dependent phenotypic suppression is accounted for by milk whey, which is present only in the latter. Inclusion of milk whey in the diet during larval stages was critical for suppression of the adult para Shu phenotypes, suggesting that this dietary modification affects development of the nervous system. We also found that milk whey has selective effects on other neurological mutants. Among the behavioral phenotypes of different para mutant alleles, those of para GEFS+ and para bss were suppressed by milk whey, while those of para DS and para ts1 were not significantly affected. Overall, our study demonstrates that different diets routinely used in Drosophila labs could have considerably different effects on neurological phenotypes of Drosophila mutants. This finding provides a solid foundation for further investigation into how dietary modifications affect development and function of the nervous system and, ultimately, how they influence behavior.